Eksplorasi Endofit Sambung Nyawa: Potensi Mikroba dalam Penemuan Obat dan Bioaktivitasnya - Salsabila Rahman (Jurnal Medika Nusantara, 2025)
Gynura procumbens, also known as “Sambung Nyawa,” is a medicinal plant known for its various therapeutic properties. This study aims to explore the potential of endophytic microbes living inside Gynura procumbens plants as a source of bioactive compounds with pharmaceutical applications. Endophytic microbes are microorganisms that live symbiotically in plant tissues without causing damage, and are known to produce secondary metabolites similar to their host plants. In this study, endophytic microbes in the form of bacteria and fungi were isolated from various plant parts, including leaves, stems, and roots. A total of 12 isolates were obtained, consisting of 7 bacteria and 5 fungi, which were identified using molecular techniques. The isolates were tested for antimicrobial, antioxidant and cytotoxic activities. The antimicrobial assay showed significant inhibitory effects against Staphylococcus aureus and Candida albicans, where isolates from the genus Streptomyces and Penicillium had the highest activity. Antioxidant activity was measured using the DPPH method, and two bacterial isolates showed strong free radical scavenging ability. Cytotoxic assays on MCF-7 breast cancer cells revealed that the fungal isolates, mainly from the genus Penicillium and Aspergillus, had strong anticancer activity. The results of this study indicate that endophytic microbes from Gynura procumbens contain bioactive compounds that have potential as antimicrobial, antioxidant, and anticancer agents. This study confirms the importance of exploring endophytic microbes from medicinal plants in the discovery of new drugs and the development of therapeutic agents. Further research is needed to isolate and characterize the specific compounds responsible for these bioactivities as well as evaluate their potential in clinical applications.